2019
DOI: 10.1007/s42729-019-00150-8
|View full text |Cite
|
Sign up to set email alerts
|

Differential Tolerance and Phenolic Leaf Profile in Response to Boron Supply in Two Highbush Blueberry Genotypes

Abstract: Highbush blueberry (Vaccinium corymbosum L.) is beneficial for human health due to its bioactive properties. Agronomic management includes boron (B) addition to promote its growth and development. We aimed to provide new insights into the effects of B supply on the phenolic profile and antioxidative capacity in the leaves of two common cultivars, Brigitta and Legacy. Seedlings of Brigitta and Legacy were supplied with different B concentrations (0-50 mg B L −1). After 30 days, leaf biomass and B content, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
(65 reference statements)
1
1
0
Order By: Relevance
“…In the current study with S. khuzistanica, the total phenol, total flavonoids and antioxidant activity assayed by DPPH and FRAP were increased in response to B. These results were consistent with the findings reported by Thurzo et al [60] in Prunus avium L. and Merino-Gergichevich et al [61] in Vaccinium corymbosum L., who also reported a positive effect of B on the total phenol and flavonoids of studied plants. Given that B has been shown to play an important role in the metabolism of phenolic compounds, the increase in phenol and flavonoids as a result of B application is not surprising [62].…”
Section: Phytochemical Evaluation and Antioxidant Activitysupporting
confidence: 93%
“…In the current study with S. khuzistanica, the total phenol, total flavonoids and antioxidant activity assayed by DPPH and FRAP were increased in response to B. These results were consistent with the findings reported by Thurzo et al [60] in Prunus avium L. and Merino-Gergichevich et al [61] in Vaccinium corymbosum L., who also reported a positive effect of B on the total phenol and flavonoids of studied plants. Given that B has been shown to play an important role in the metabolism of phenolic compounds, the increase in phenol and flavonoids as a result of B application is not surprising [62].…”
Section: Phytochemical Evaluation and Antioxidant Activitysupporting
confidence: 93%
“…For blueberry research demonstrated that B enhanced crop biomass concerning plantlets and was conducive to phenolic compounds production such as chlorogenic acid, ferulic acid, myricetin and quercetin (MERIÑO-GERGICHEVICH et al, 2017;MERIÑO-GERGICHEVICH et al, 2019). Nevertheless, the influences of B in the blueberry micropropagation and its physiological functions on enzymatic activity are not clear yet.…”
Section: Introductionmentioning
confidence: 99%